2019
DOI: 10.3389/fpls.2019.00985
|View full text |Cite
|
Sign up to set email alerts
|

The Nuts and Bolts of PIN Auxin Efflux Carriers

Abstract: The plant-specific proteins named PIN-FORMED (PIN) efflux carriers facilitate the direction of auxin flow and thus play a vital role in the establishment of local auxin maxima within plant tissues that subsequently guide plant ontogenesis. They are membrane integral proteins with two hydrophobic regions consisting of alpha-helices linked with a hydrophilic loop, which is usually longer for the plasma membrane-localized PINs. The hydrophilic loop harbors molecular cues important for the subcellular localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 152 publications
1
75
0
Order By: Relevance
“…Functional site analysis within L. chinense PIN conserved motifs Through previous experimental veri cation and data analysis, several functional elements and sites that control PIN protein polarity, tra cking and activity have been identi ed [3,31,32]. Our multiple sequence alignments show that these elements reside for a large part within the highly conserved LcPIN sequence motifs ( Fig S2).…”
Section: Lcpin Geneshave Highly Conserved Motifs and Evolutionary Relmentioning
confidence: 78%
See 3 more Smart Citations
“…Functional site analysis within L. chinense PIN conserved motifs Through previous experimental veri cation and data analysis, several functional elements and sites that control PIN protein polarity, tra cking and activity have been identi ed [3,31,32]. Our multiple sequence alignments show that these elements reside for a large part within the highly conserved LcPIN sequence motifs ( Fig S2).…”
Section: Lcpin Geneshave Highly Conserved Motifs and Evolutionary Relmentioning
confidence: 78%
“…The structure domain and membership division of LcPIN protein PIN genes have been studied in detail in A. thaliana: they are mainly composed of two conserved hydrophobic loops in the N-and C-terminus and a variable hydrophobic loop in the middle [31]. By analyzing the transmembrane domain and conserved motifs in LcPIN proteins, we found that most of the transmembrane structures of LcPINs contain 5-9 transmembrane spirals except LcPIN6b.…”
Section: Basic Information and Evolutionary Relationship Of Lcpin Genmentioning
confidence: 99%
See 2 more Smart Citations
“…Rademacher and Offringa, 2012;Barbosa et al, 2018;Zwiewka et al, 2019). Also PIN 292 ubiquitination (on lysines) and controlled proteolytic degradation act in auxin-mediated 293 processes(Leitner et al, 2012).…”
mentioning
confidence: 99%